The Chronic of the Chronic of the Board of Instructions in the Work of Djamil Suherman a Study of the Sociology of Literature - Rohim Rohim; Purwaningsih Purwaningsih; Dea Letriana Cesaria (Budapest International Research and Critics University, 2022)
Pesantren literature once triumphed in the '30s through works created by the pesantren themselves, whether or not they present an Islamic boarding school background. One such era was represented by Djamil Suherman. After that period, the literary world was more concerned with the critical attitude of literary writers to the government during the transition to independence. Entering the 2000s, Islamic boarding school literature began to come to life again along with the birth of young writers with a santri background, including Acep Zamzam Noer and Habiburrahman El Shirazy. However, before the two of them came to the fore, Djamil Suherman appeared first through his work pouring religious moral ideas through literature. This writing will reveal Djamil Suherman's actions in carrying out the mission of the pesantren in the midst of the complex challenges of the times, and it is hoped that the results will provide a picture of the worthy khal, that the pesantren world is an integral part of the development of Indonesian literature.